PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN KARTU KATA BAGI SISWA SMP NEGERI 1 JUMO TEMANGGUNG (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
The objective that is going to be reached through the Classroom-Action Research is to find out how far the word card technique application influences the learning of poetry writing on the students of Secondary School. The research was conducted on the VII F students of SMP Negeri 1 Jumo Kabupaten Temanggung during semester II of 2015/2016 school year. Around 32 students were the subjects of the research conducted by using word cards in the learning of Bahasa Indonesia at the aspect of poetry writing skill. The procedure in the research on the students in the learning process of poetry writing was taken through two cycles, and each one consists of four phases, i.e.: planning, action taking, observation, and reflection. The data collection was made by assessing the students’ works before and after applying word card technique. The methods which were used in the research were discussion and giving poetry writing assignment. The research shows change occurrence of the VII F students’ ability to write poetries. The VII F students before applying the word card technique were less motivated, and even there were only 22 students (67.75%) meeting the Minimum Criteria of Mastery Learning standard. After using the word cards as teaching tools in the learning of poetry writing, the VII F students got more motivated and so active that Minimum Criteria of Mastery Learning standard could reach 29 students or 90.63 %. This shows the improvement occurrence about 21.87 %, in the other words those who reached grade point 75 as Minimum Criteria of Mastery Learning increased up to 7 students.